2013
DOI: 10.1007/s00204-013-1131-4
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic-induced cancer cell phenotype in human breast epithelia is estrogen receptor-independent but involves aromatase activation

Abstract: Accumulating data suggest arsenic may be an endocrine disruptor, and tentatively linked to breast cancer by some studies. Therefore, we tested the effects of chronic inorganic arsenic exposure on the normal, estrogen receptor (ER)-negative breast epithelial cell line, MCF-10A. Cells were chronically exposed to a low-level arsenite (500 nM) for up to 24 weeks. Markers of cancer cell phenotype and expression of critical genes relevant to breast cancer or stem cells (SCs) were examined. After 24 weeks, chronic ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 44 publications
(78 reference statements)
1
32
0
Order By: Relevance
“…In contrast, treatment of cells in culture usually involves a single, much shorter exposure to arsenic which often necessitates the use of higher than physiological concentrations to observe measurable effects. Chronic treatment of cells with low concentrations of arsenite can induce cellular transformation [8992], global DNA hypomethylation [9093], local DNA hypermethylation [93, 94], alterations in chromatin structure and splicing patterns [89], and increases in oncogenic gene expression [91, 95]. Recent research has indicated that chronic arsenic exposure alters methylation patterns of DNA repair factors involved in NER, leading to reduced RNA expression of ERCC1 and ERCC2 [96].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, treatment of cells in culture usually involves a single, much shorter exposure to arsenic which often necessitates the use of higher than physiological concentrations to observe measurable effects. Chronic treatment of cells with low concentrations of arsenite can induce cellular transformation [8992], global DNA hypomethylation [9093], local DNA hypermethylation [93, 94], alterations in chromatin structure and splicing patterns [89], and increases in oncogenic gene expression [91, 95]. Recent research has indicated that chronic arsenic exposure alters methylation patterns of DNA repair factors involved in NER, leading to reduced RNA expression of ERCC1 and ERCC2 [96].…”
Section: Discussionmentioning
confidence: 99%
“…Some in vitro and in vivo studies show cadmium and arsenic to mimic estrogen activity via the classic pathway mediated by ERs, 35-37 while more recent studies show that both arsenic and cadmium can induce basal-like cancer cell phenotypes in hormone-receptor-negative breast epithelial cell lines. 38,39 Additionally, evidence has supported mechanisms independent of ERs in estrogen-mediated breast cancer development through production of genotoxic estrogen metabolites (such as catechols and quinines), which can cause DNA damage and/or form DNA adducts. 34 These observations provide some biologic rationale to support the findings in the present study implicating exposure to arsenic or cadmium for risk of hormone-receptor-negative breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CATLE cells also showed loss of expression of the tumor suppressor gene PTEN (Carracedo et al, 2011; Cooper et al, 2013), and the putative tumor suppressor gene SLC38A3 (Kholodnyuk et al, 2006), together with increased expression of the oncogene KRAS and increased expression of AKT1, a central member of a frequently activated signaling pathway in cancer (Carpten et al, 2007). Loss of PTEN expression and over-expression of KRAS are common in human lung cancer (Zhu et al, 2014; Kadara et al, 2012; Cooper et al 2013) and common in arsenic-induced malignant transformation of other cell types (Benbrahim-Tallaa et al, 2005; Tokar et al, 2010a; Ngalame et al, 2014a,b; Xu et al, 2014). ERK1/2 and p-ERK, which are critical to cell proliferation, are commonly activated in cancers and linked to RAS activation (e.g.…”
Section: Discussionmentioning
confidence: 99%